Penyusunan Laporan Keuangan Berdasarkan SAK EMKM Berbantuan Microsoft Excel 2016 - Muhammad Husnur Rofiq; Rahma Nazila Muhammad (Indonesian Accounting Literacy Journal, 2022)
This purpose of this study was to determine the accounting system, to determine the design of the bookkeeping process, and to design the preparation of financial statements based on the Financial Accounting Standards for Micro, Small, and Medium Entities (SAK EMKM) at Laila Collection MSMEs. The research method used in this study is a qualitative method with a descriptive approach. Data collection techniques are carried out through observation, interviews, and documentation. The results of this study indicate that the company has just recorded for employee salaries, calculation of the cost of production, and details of customer orders and has not prepared financial reports in accordance with applicable standards. So to solve these problems, the author designs the bookkeeping process and makes a draft of the preparation of financial statements using Microsoft Excel 2016. The reports prepared by the authors are the report on the cost of production, the income statement, the statement of financial position, and notes to the financial statements in accordance with SAK EMKM in April 2021. With this research, it is hoped that Laila Collection MSMEs can know and be able to prepare financial reports in accordance with SAK EMKM.